EMPOWERING SMES BASED ON SHARIA ECONOMY THROUGH FINANCIAL MANAGEMENT TRAINING IN COMMUNITY ENVIRONMENT AROUND RIZKI BAKTI NEGERI FOUNDATION IN PEKANBARU - Saputra, Wali (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
This community service initiative is designed to enhance the capabilities of Micro, Small, and Medium Enterprises (MSMEs) in proximity to the Rizki Bakti Negeri Foundation in Pekanbaru through training in financial management informed by sharia economic principles. A total of 35 MSME participants engaged in the training, which comprised four primary sessions: an introduction to sharia economics, foundational financial management, basic accounting principles, and a simulation of sharia-compliant financial management practices. Methodologies that are participatory and contextually relevant were employed to facilitate an optimal comprehension of the material presented. The evaluation outcomes indicated a marked improvement in the participants’ knowledge and competencies concerning the management of their business finances in accordance with sharia. Furthermore, participants exhibited a strong commitment to implementing the principles of sharia finance and establishing a collaborative learning community. This initiative demonstrates that education grounded in Islamic values, alongside practical methodologies, is significantly effective in fostering the sustainable enhancement of the local economy. It is anticipated that this initiative will serve as a replicable model in other regions and contribute to a broader strategy aimed at empowering the local economy.